Charge‐Transfer Complex Crystal Based on Extended‐π‐Conjugated Acceptor and Sulfur‐Bridged Annulene: Charge‐Transfer Interaction and Remarkable High Ambipolar Transport Characteristics. (24th March 2014) - Qin, Yunke; Zhang, Jing; Zheng, Xiaoyan; Geng, Hua; Zhao, Guangyao; Xu, Wei; Hu, Wenping; Shuai, Zhigang; Zhu, Daoben
<x xml:space="preserve">Abstract</x> A single crystal of a novel mixed‐stack donor–acceptor complex formed by a tetracyanoquinodimethane derivative with an extended π‐conjugated system and a sulfur‐bridged annulene displays the highest ambipolar transport behavior among donor–acceptor complexes reported with electron and hole mobilities reaching up to 0.24 and 0.77 cm2 V−1 s−1, respectively. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>